55. Assessing the risk of restless legs syndrome in small fiber peripheral neuropathy. Issue 12 (December 2017) - Rinaldi, F.; Damioli, S.; Pasolini, M.; Maria, G. De; Padovani, A.; Filosto, M.
Abstract : The pathophysiology of restless legs syndrome (RLS) isn't completely understood. Small Fiber Neuropathy (SFN) patients may have RLS-like sensory symptoms. The aim of this study was to assess the prevalence and clinical features of RLS in patients with SFN, compared with Large Fibres Neuropathy (LFN) patients and healthy controls. All patients underwent nerve-conduction studies and electromyography, and a skin biopsy to confirm SFN. RLS was diagnosed according to international criteria. We compared: frequency of RLS, age of onset, severity as measured by IRLS, insomnia and diabetes comorbidity. We included 39 SFN patients, 37 LFN patients and 40 matched controls. Peripheral nerve-conduction velocities were normal in SFN patients and controls. SFN patients had a 25.60% prevalence of RLS, compared to 10.80% in LFN and 7.50% in controls. Age of onset was 42.91 years, versus 62.67 in LFN and 58.50 in controls. Mean IRLS was 15.6 versus 19.5 in LFN and 18.6 in controls. The occurrence of insomnia was similar between SFN and LFN (43.58% and 43.24%), but higher than in controls (20%). Biopsy-proven SFN patients had a higher risk for an early-onset RLS. They show a less severe RLS, but it can frequently cause insomnia.